Hesitancy versus acceptability: An observational study for acceptance of COVID-19 vaccine among parents and guardians of children under 17 years age in South East Rajasthan - Sharma, Ashutosh; Gupta, Vinita; Sharma, Anita; Sharma, Saurabh (Asian Journal of Medical Sciences, 2022)
Background: Vaccination against COVID-19 is necessary to reach herd immunity and essential for mitigating the spread. To establish herd immunity, the immunity generated by natural infection or vaccination must prevent onward transmission, not just clinical disease. However, several studies have shown that achieving herd immunity through natural infection might be difficult. Aims and Objectives: The aim of the study is to enquire about parental acceptability for COVID-19 vaccination for their children, factors affecting acceptability, perceptions for pediatric COVID-19 vaccines. Materials and Methods: We conducted an online questionnaire survey in mode of Google form which was distributed through social media platforms to parents/guardians of children below 17 years of age in months of November and December 2021. The questionnaire had various sections: Socio demographic characteristics, family members and medical history, COVID-19-related history, attitudes toward COVID-19, attitudes toward COVID-19 vaccines, and acceptance of COVID-19 vaccination for their children. Results: The most of the parents (71.77%) were ready to vaccinate their child. Graduated parents were showing maximum acceptance. Variables related to maximum vaccine acceptance include English medium of education, higher income, COVID-19-positive member in family, vaccinated parents/guardians, and vigilant parents/guardians about child COVID vaccination. In case of side effects, 68.05% of responders agreed to follow the professional advice of personal doctor/vaccinator. About 35% of respondents want government to roll out vaccination in a phased manner. About 69% responders are in favor of making hospitals and schools as COVID-19 vaccination center for children. Conclusion: The study found high multifactorial acceptability for pediatric COVID-19 vaccination which should be rolled out in phased manner.